BEHAVIORAL FINANCE DALAM PENGAMBILAN KEPUTUSAN - Dwi Perwitasari Wiryaningtyas (UNEJ e-Proceeding)
Make a right and wise decision is a major aspect in running a business or venture. As a decision maker an investor can make different decision, it is because an investor in making decisions do not always behave rationally. Many different kinds of research on behavioral finance recent decades shows that investors often act irrationally in decision making even in a market phenomenon capital or financial markets financial investor behavior contrary to the standards and economics behavioral finance theory began to replace the concept of financial standards and replace the concept of rational investors become normal investor who has a bias deviations in social, cognitive, and emotional. Behavioral finance and decision making is strongly associated with psychological factors and also how much risk would be the investor.